2020
DOI: 10.1302/1863-2548.14.190153
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Legg-Calvé-Perthes disease following proximal femoral varus osteotomy performed in the avascular necrosis stage: A prospective study

Abstract: Purpose This prospective study was undertaken to describe patterns of fragmentation of the femoral epiphysis following a proximal femoral varus osteotomy (PFVO) done during stage I of LCPD and to assess the disease duration and outcome in each pattern. Methods A total of 25 children treated by a PFVO in stage I of LCPD were followed until healing. The MRI Perfusion Index, radiographic changes in the femoral epiphysis, disease duration and the Sphericity Deviation Score (SDS) at healing were documented. The rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 25 publications
1
43
0
1
Order By: Relevance
“…The percentages of 2 patterns of typical fragmentation and atypical fragmentation with horizontal fissure appreciably differed between hips treated with SIO and FVO, with the former being higher in this study (67% vs. 5%) and the latter being higher in a previous study (48% vs. 16%). 9 Whether this discrepancy relates to only different osteotomy sites warrants further investigation by use of other cohorts treated with early SIO. Besides the impact on the amount of blood flow, these 2 osteotomies differ in terms of the load vector-altering effect for the capital femoral epiphysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentages of 2 patterns of typical fragmentation and atypical fragmentation with horizontal fissure appreciably differed between hips treated with SIO and FVO, with the former being higher in this study (67% vs. 5%) and the latter being higher in a previous study (48% vs. 16%). 9 Whether this discrepancy relates to only different osteotomy sites warrants further investigation by use of other cohorts treated with early SIO. Besides the impact on the amount of blood flow, these 2 osteotomies differ in terms of the load vector-altering effect for the capital femoral epiphysis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because of the retrospective nature of the study, the intervals between serial radiographs were not standardized, probably leading to a greater overestimation of the actual stage duration than other prospective studies. 8,9 All school-aged patients, however, were examined every long holiday twice or 3 times a year until skeletal maturity, and patients and their parents were usually requested to visit 1 or 2 more times during the school day until implant removal. This examination schedule corresponds to 3 or 4-month intervals during the active stage of the disease and afterward at least 6 months intervals, being comparable with that of other prospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is echoed in the recent publication by Singh et al . [28], who suggested that an extended period of weight-relief after proximal femoral varus osteotomy may help prevent fragmentation and collapse of the epiphysis and thus preserve the recanalization vessels previously described by Conway [29] as being predictive of a good outcome. Previous investigations into the pathogenesis of femoral head deformity using a piglet model of ischemic osteonecrosis [4,5] demonstrated decreased mechanical strength of the femoral head due to increased bone resorption and decreased bone formation during the repair phase of the model, which resembles the fragmentation stage of LCPD.…”
Section: Discussionmentioning
confidence: 99%
“…Within paediatric orthopaedics, numerous conditions encompass follow-up which involves radiographic imaging. The risk associated with routine follow-up of patients with Perthes Disease or hip surveillance in Cerebral Palsy is ground for future research [ 30 , 31 ] . Whilst radiographs are so important for complete assessment, this study supports that the radiation principles ‘As Low As Reasonable Achievable (ALARA)’ are being adhered to for DDH follow-up [ 32 ].…”
Section: Discussionmentioning
confidence: 99%